Ecological aspects of manganese geochemistry in the zone of mining waste heaps technogenesis - Kochmar, Iryna N.; Karabyn, Vasyl V. (Journal of the Belarusian State University. Ecology, 2018)
In this article the assessment of the environmental hazards in the zone affected by the Vizeiska Mine is presented. The main reason of its negative effect is caused by the distribution of various forms of manganese in the rocks of the waste heaps. The assessment is based on the establishment of the patterns of manganese form distribution in the technogenesis zone. The concentrations of manganese in total form and in hydrochloric acid, acetate-ammonium and water-soluble extracts are established in mudstones, siltstones, sandstones, coal waste heaps and soils in the technogenesis zone of the mine. The content of total forms of manganese in the rocks of the Vizeyska mine waste heaps changes from 118,61 mg/kg to 3849,61 mg/kg and an average content is 1181,14 mg/kg. Relative to the total form, the concentration coefficients of manganese in the hydrochloric acid extract vary from 0,014 to 0,242 in rocks and from 0,86 to 0,94 in soils; in acetate ammonium – from 0.020 to 0.177 in rocks and from 0,23 to 0,34 in soils; in the water extract – from 0,0005 to 0,072 in the rocks. The patterns of variation in the concentration of different migration forms of manganese between unburnt and burnt rocks, as well as in rocks of different granulometric composition, are established. The results of the research give an opportunity for evaluating the rocks of the Vizeyska Mine waste heaps in the area, where various forms of manganese is present in rocks and soils. These rocks are suitable for use and safe for the environment.
Keywords: coal-mining; heavy metals speciation; environmental safety; geochemistry of manganese; migration